Anchovy Rice Nuggets and Straw Mushroom with Porang Flour Substitution to Prevent Stunting - Junendri Ardian; Anisah Anisah; Widani Darma Isasih; M. Thonthowi Jauhari (Biology, Medicine, & Natural Product Chemistry, 2026)
Stunting is one of the chronic nutritional problems in toddlers that remains highly prevalent in Indonesia. Prevention efforts can be carried out through the innovation of functional foods based on nutrient-rich local ingredients. This study aimed to determine the effect of porang flour substitution on the hedonic quality, toddler panelists’ acceptance, and nutritional composition of anchovy rice and straw mushroom nuggets. The study used an experimental design with three formulas: P1 (60% anchovy rice, 25% straw mushroom, 20% porang flour), P2 (60% anchovy rice, 20% straw mushroom, 25% porang flour), and P3 (60% anchovy rice, 15% straw mushroom, 30% porang flour). Hedonic and hedonic quality tests were conducted on 25 toddler panelists, while proximate analysis included moisture, ash, fat, protein, crude fiber, and carbohydrate content. The results showed that P1 obtained the highest scores and was most preferred in terms of color, aroma, taste, and texture. Proximate analysis also showed that P1 had the highest protein content (6.81%) with 65.82% moisture, 1.56% fat, 2.33% ash, 0.95% crude fiber, and 23.47% carbohydrates. Meanwhile, the increased substitution of porang flour in P3 reduced sensory quality and protein levels, although it increased fiber and carbohydrates. Therefore, P1 can be considered the best formula because it achieved the highest acceptance and provided more suitable nutrients to support the improvement of toddlers’ nutritional status. This study highlights that the utilization of local food ingredients such as anchovy rice, straw mushrooms, and porang flour has the potential to serve as an innovative strategy for stunting prevention.